Hypersensitivity of Prelimbic Cortex Neurons Contributes to Aggravated Nociceptive Responses in Rats With Experience of Chronic Inflammatory Pain - Fan, Xiao-Cen; Fu, Su; Liu, Feng-Yu; Cui, Shuang; Yi, Ming; Wan, You (Frontiers in Molecular Neuroscience, 2018)
Previous experience of chronic pain causes enhanced responses to upcoming noxious events in both humans and animals, but the underlying mechanisms remain unclear. In the present study, we found that rats with complete Freund’s adjuvant (CFA)-induced chronic inflammatory pain experience exhibited aggravated pain responses to later formalin test. Enhanced neuronal activation upon formalin assaults and increased phosphorylated cAMP-response element binding protein (CREB) were observed in the prelimbic cortex (PL) of rats with chronic inflammatory pain experience, and inhibiting PL neuronal activities reversed the aggravated pain. Inflammatory pain experience induced persistent p38 MAPK (p38) but not extracellular regulated protein kinase (ERK) or c-Jun N-terminal kinase (JNK) hyperphosphorylation in the PL. Inhibiting the p38 phosphorylation in PL reversed the aggravated nociceptive responses to formalin test and down-regulated enhanced phosphorylated CREB in the PL. Chemogenetics identified PL–periaqueductal grey (PAG) but not PL–nucleus accumbens (NAc) as a key pathway in inducing the aggravated formalin pain. Our results demonstrate that persistent hyperphosphorylation of p38 in the PL underlies aggravated nociceptive responses in rats with chronic inflammatory pain experience.